Мультикультурализм и проблема этнокультурных оснований человеческого бытия - Аполлонов, Иван (Զանգակ հրատ.)
The article discusses the ontological foundations of global, multicultural society. The social code of the society determines the deconstruction of the metaphysical hierarchy of the culture that distinguishes between genuine and imaginary levels of the human being. The value orientations of this society is self-expression in consumption, which implies the self-value of the diversity of cultural peculiarities. Culture ceases to be a way of asserting the moral basis of man and becomes a form of self-expression. In this context, ethnic culture takes quasirotational forms exotic brand and is a means of group cohesion, an instrument of struggle for economic and political preference in a global society of mass consumption. Another vector for the treatment of modern man to the traditional forms of culture associated with the search for spiritual grounds the authenticity of his own existence in the world of simulacra and the global sham. This base is an apophatic holism, in which the integrity of the tradition defines the horizon of universal values embodied in the folk customs. Հոդվածում քննարկվում է բազմամշակութայնության հիմնախնդիրը՝ այն զուգահեռելով մարդկային կեցության էթնոմշակութային հիմքերին: Բազմամշակութայնությունը դիտարկվում է իբրև գլոբալիզացիայի կաևորագույն սոցիալական պարադոքս, քանզի ինտեգրատիվ գործընթացների հարթության վրա, այն շոշափում է հասարակական կյանքի գրեթե բոլոր ոլորտները:
Keywords: Культура; Этнокультура